Evasive shareholder meetings - Li, Yuanzhi; Yermack, David (Journal of Corporate Finance, 2016)
We study the strategic scheduling of annual shareholder meetings. When companies move their annual meetings a great distance from headquarters, they tend to experience pronounced stock market underperformance in the six months after the meeting and announce earnings below expectations over the subsequent year. Companies appear to schedule meetings in remote locations when the managers have private, adverse information about future performance and wish to discourage scrutiny by shareholders, analysts, and the media. However, shareholders do not decode this signal, since the disclosure of meeting locations leads to little immediate stock price reaction. We find that voter participation drops when meetings are held at unusual hours, even though most voting is done electronically during a period of weeks before the meeting convenes.